(untitled) (Heritage, 2025)
This work represents a pioneering effort to look at Serbian-Kazakh cultural ties. Namely, since Kazakh language, literature and culture are not studied at humanities faculties in Serbia, nor Serbian language, literature and culture at related faculties in Kazakhstan, any occurrence of mutual cultural intertwining is a peculiar phenomenon. However, in the 2010s, information about the existence of cultural ties between Serbia and Kazakhstan appeared in the rhetoric of Serbian politics, and a memorial bust of the Kazakh poet Zhambil Zhabajev was established in New Belgrade in 2016. Therefore, the aim of this paper is to answer the questions of whether there are Serbian-Kazakh cultural connections, how developed they are, who are their representatives and workers. Also, to analyze the current situation in the same and the real possibilities of their improvement. The paper relies on relevant scientific and auxiliary literature that depicts the cultural intertwining of the Serbian and Kazakh people.